Evaluation of multi-stage fracturing a horizontal well of low permeability reservoirs in East China Sea - ZHANG Fengxi, NIU Congcong, ZHANG Yichi (Youqicang pingjia yu kaifa)
Staged fracturing technology for offshore horizontal wells is still in an exploratory phase due to operational limitations. The effectiveness of fracturing horizontal wells has a significant impact on their productivity. Therefore, evaluating the fracturing effect and guiding the fracturing development of horizontal wells is a pressing concern. This paper firstly introduced the geological situation of low permeability reservoir in the East China Sea in detail, and the process of stage fracturing of the first open hole horizontal well was described. Then the fracturing effect of the multi-stage fractured horizontal well was evaluated successfully using the latest fracturing effect evaluation method of SPEE（Society of Petroleum Evaluation Engineers）. By analyzing the fracturing operation parameters of the well and comparing EUR（Estimated Ultimate Recovery） before and after fracturing, the fracturing effect evaluation method is verified to prove the correctness and reliability. Finally, it is concluded that the gas recovery rate of this horizontal well after fracturing is increased by 9.3 % and the oil recovery rate is increased by 6.6 %. The successful implementation of staged fracturing and the subsequent evaluation of its effects on the first horizontal well in the East China Sea set the stage for future development of horizontal well staged fracturing in offshore low-permeability reservoirs.